The campaign against Female Genital Cutting: empowering women or reinforcing global inequity? - Latham, Susannah Jane (Routledge, 2016)
This paper explores the issue of Female Genital Cutting (FGC), starting with the story of how the practice changed and was permanently abandoned in a single generation in a rural Iranian town in the 1950s. Two striking features of this example—its direction by religious men, and the shift to less severe forms of FGC before total abandonment—challenge contemporary orthodoxy on ending FGC. Further, the minimal impact that this FGC abandonment had on the lives of girls and women raises the question of whether the attention and resources currently spent on FGC abandonment programmes might provide a greater benefit to communities if spent differently. In the context of most FGC practicing communities facing multiple significant challenges to their well-being, including food shortages, extreme poverty and poor health and education infrastructure, this paper asks whether ending FGC is as high a priority for practicing communities as it is for the international donors who largely fund abandonment programmes.